Synthesis, Antimycobacterial Activity and In Vitro Cytotoxicity of 5-Chloro-N-phenylpyrazine-2-carboxamides - Jan Zitko; Barbora Servusová; Pavla Paterová; Jana Mandíková; Vladimír Kubíček; Radim Kučera; Veronika Hrabcová; Jiří Kuneš; Ondřej Soukup; Martin Doležal (Molecules, 2013)
5-Chloropyrazinamide (5-Cl-PZA) is an inhibitor of mycobacterial fatty acid synthase I with a broad spectrum of antimycobacterial activity in vitro. Some N-phenylpyrazine-2-carboxamides with different substituents on both the pyrazine and phenyl core possess significant in vitro activity against Mycobacterium tuberculosis. To test the activity of structures combining both the 5-Cl-PZA and anilide motifs a series of thirty 5-chloro-N-phenylpyrazine-2-carboxamides with various substituents R on the phenyl ring were synthesized and screened against M. tuberculosis H37Rv, M. kansasii and two strains of M. avium. Most of the compounds exerted activity against M. tuberculosis H37Rv in the range of MIC = 1.56–6.25 µg/mL and only three derivatives were inactive. The phenyl part of the molecule tolerated many different substituents while maintaining the activity. In vitro cytotoxicity was decreased in compounds with hydroxyl substituents, preferably combined with other hydrophilic substituents. 5-Chloro-N-(5-chloro-2-hydroxyphenyl)pyrazine-2-carboxamide (21) inhibited all of the tested strains (MIC = 1.56 µg/mL for M. tuberculosis; 12.5 µg/mL for other strains). 4-(5-Chloropyrazine-2-carboxamido)-2-hydroxybenzoic acid (30) preserved good activity (MIC = 3.13 µg/mL M. tuberculosis) and was rated as non-toxic in two in vitro models (Chinese hamster ovary and renal cell adenocarcinoma cell lines; SI = 47 and 35, respectively).